Bipolar patterns of intraspecific competition in bryozoans - Barnes, David K A; Kuklinski, Piotr (Marine Ecology Progress Series, 2005)
Polar shores probably represent the most dynamic and extremely disturbed environments on the globe. Nevertheless intense battles amongst sessile organisms for space are commonplace on hard substrata, mainly between fast-growing pioneer species. In this study we examined spatial interactions in encrusting species at 3 sites within each of 2 high Arctic localities, Horsundfjord (77°N) and Kongsfjord (79°N) in Spitsbergen, and 2 Antarctic localities, Signy Island (60°S) and Adelaide Island (68°S). In both polar regions 1 to 11% of encrusting fauna were involved in intraspecific interactions. Intraspecific competition was common; it usually involved just 1 or 2 pioneer species, mainly ended in tied outcomes, and most variability was at a local scale. The proportion of intraspecific encounters varied considerably at local (km) scales (19 to 99% intraspecific at different sites), reflecting an extremely patchy environment due to ice scour. Most intraspecific encounters resulted in ties (stand-offs) and again most variability was at a local scale. Many intraspecific encounters were constructive, forming large (>1 m3) foliaceous colonies (termed bioconstructions) whose 3D structures can harbour rich biotas. In other colonies intraspecific competition caused crowding and accelerated ovicell production (reproductive activity). Homosyndrome (fusion) was not observed in the Arctic and was rare in the Antarctic, where its frequency differed significantly between competitor identities. We found that the likelihood of meeting conspecifics versus other species and of tied outcomes in encounters was related to the performance of species in interspecific competition: ties were most common, and homosyndrome only occurred in poor competitors. In the context of rapid Arctic and west Antarctic warming and ice-loading of nearshore waters, we predict strongly changing patterns of intraspecific competition. Indeed we suggest that decreased patchiness of intra- versus interspecific competition and decreased levels of intraspecific competition should be strong indicators of increases in surface water ice-loading from ice-sheet collapses. KEYWORDS: Sublittoral · Benthos · Bioconstruction · Climate change · Homosyndrome
Keywords: Sørishavet; bentiske organismer; bryozoa; klimaendringer; marin biologi; miljøendringer; oseanografi; polarområdene

Physical properties and stratigraphy of surface snow in western Dronning Maud Land, Antarctica - Kärkäs, Eija; Martma, Tõnu; Sonninen, Eloni (Polar Research, 2005)
Information about the spatial variations of snow properties and of annual accumulation on ice sheets is important if we are to understand the results obtained from ice cores, satellite remote sensing data and changes in climate patterns. The layer structure and spatial variations of physical properties of surface snow in western Dronning Maud Land were analysed during the austral summers 1999/2000, 2000/01 and 2003/04 in fi ve different snow zones. The measurements were performed in shallow (1 - 2 m) snow pits along a transect extending 350 km from the seaward edge of the ice shelf to the polar plateau. These pits covered at least the last annual accumulation and ranged in elevation from near sea level to 2500 m a.s.l. The ?18O values and accumulation rates had a good linear correlation with the distance from the coast. The mean accumulation on the ice shelf was 312 ± 28 mm water equivalent (w.e.); in the coastal region it was 215 ± 43 mm w.e. and on the polar plateau it was 92 ± 25 mm w.e. The mean annual conductivity and grain size values decreased exponentially with increasing distance from the ice edge, by 48 %/100 km and 18 %/100 km respectively. The mean grain size varied between 1.5 and 1.8 mm. Depth hoar layers were a common phenomenon, especially under thin ice crusts, and were associated with low dielectric constant values.
Keywords: Dronning Maud Land; geofysikk; geologi; havnivå; innlandsis; klimatologi; miljøendringer; overflatesnø; snø akkumulasjon; stratigrafi

Postglacial marine environmental changes in Maxwell Bay, King George Island, West Antarctica - Khim, Boo-Keun; Yoon, Ho Il (Polar Research, 2003)
Sediment textural properties and total organic carbon (TOC) contents of three sediment cores from Maxwell Bay, King George Island, West Antarctica, record changes in Holocene glaciomarine sedimentary environments. The lower sedimentary unit is mostly composed of TOC-poor diamictons, indicating advanced coastal glacier margins and rapid iceberg discharge in proximal glaciomarine settings with limited productivity and meltwater supply. Fine-grained, TOC-rich sediments in the upper lithologic unit suggest more open water and warm conditions, leading to enhanced biological productivity due to increased nutrient-rich meltwater supply into the bay. The relationship between TOC and total sulfur (TS) indicates that the additional sulfur within the sediment has not originated from in situ pyrite formation under the reducing condition, but rather may be attributed to the detrital supply of sand-sized pyrite from the hydrothermal-origin, quartz-pyrite rocks widely distributed in King George Island. The evolution of bottom-water hydrography after deglaciation was recorded in the benthic foraminiferal stable-isotopic composition, corroborated by the TOC and lithologic changes. The Ø18O values indicate that bottom-water in Maxwell Bay was probably mixed gradually with intruding 18O-rich seawater from Bransfield Strait. In addition, the Ø13C values reflect a spatial variability in the carbon isotope distribution in Maxwell Bay, depending on marine productivity as well as terrestrial carbon fluxes by meltwater discharge. The distinct lithologic transition, dated to approximately 8000 yr BP (uncorrected) and characterized by textural and geochemical contrasts, highlights the postglacial environmental change by a major coastal glacier retreat in Maxwell Bay.
Keywords: Sørishavet; geofysikk; geokjemi; marin geologi; miljøendringer; sedimenter